JOB AVAILABILITY AND ENTREPRENEURSHIP EDUCATION AMONG UNDERGRADUATE UNIVERSITY STUDENTS IN KENYA - Ngigi, Bilha Wambui; Gichunge, Dr. Evangeline M.; Orero, Dr.Risper (International Journal of Entrepreneurship and Project Management, 2020)
Purpose: The purpose this study was to ascertain the connection shared by job availability factors and entrepreneurship education as a specialization among undergraduate students within universities in Kenya. Methodology: This research was designed as a descriptive survey, correlation quantitative research. The study population of 2,043 students was drawn from 3rd year undergraduate business students who had already selected their areas of specialization. The Krejcie & Morgan sample formula for finite samples was used to yield a sample of 327 students that participated in the research. Questionnaires were the primary data collection instrument and the collected data was modeled through regresssion model and analyzed using SPSS version 24. Results: Job availability and entrepreneurship education are positively and significantly related (Î² =0.406, p=0.000). Therefore, a unit increase in job availability would lead to increase in preference for entrepreneurship education by 0.406. Factors like career utility, probability of advancing in one's occupation, flexibility in terms of work-life balance; economic growth and stability; and the unemployment levels in Kenya are the major driving forces in determining an area of specialization for students. Unique contribution to policy and practice: The study recommends that students should look at themselves as a consolidation of traits and skills and not just an occupation. This will help them achieve major skills an entrepreneur which are versatility, agility, innovativeness, determination, relationship and communication skills, the ability to constantly study and improve on previous drawbacks, and the ability to manage work, time, and money.